Interventions for increasing medication adherence in heart failure patients: A narrative review - Jelinek, Libor; Vaclavik, Jan; Lazarova, Marie (Biomedical papers, 2024)
Heart failure is one of the critical and most costly medical challenges of the 21st century. It is a chronic debilitating condition and adherence to medication, a precondition for successful treatment is often poor. There are various interventions for improving the adherence. Depending on the goal of the intervention, these are roughly patient centric, healthcare provider centric and system centric. We provide an overview of these interventions with a focus on effectiveness and appropriateness in different clinical situations. Their use can lead to improved patient outcomes and reduced economic burden of the disease.
Keywords: pharmacotherapy; heart failure; barriers to adherence; interventions to improve adherence